(untitled) (International Journal of Engineering and Computer Science, 2015)
The prominence of digital image processing domain has been increased from last few decades due to its advanced research areas such as medicine, biometrics, military, robotics etc. In this work an important issue has taken as area of research namely protecting the privacy information from the unauthenticated users either as accidental or incidental ways. Although tremendous progress has been made in the past years on the protecting the privacy information by make use of biometrics namely fingerprint, palm print, iris etc. The usage of fingerprint in academia, medical labs, military has been increased from few years but in some scenarios these fingerprint mechanisms fails to meet the practical requirement. The proposed work presents an novel work where dual fingerprint mechanisms is utilized to protect the privacy information where the orientation from one fingerprint and miniature from another finger print has been taken into account to develop an template which looks alike of original fingerprint..The proposed template protects the information from the theft and as well as shows low error rate FRR= 0.4% at FAR= 0.1%. over traditional approaches. Finally when compared with conventional methods proposed method has better virtual identity which shows good results against incidental and accidental attacks.